Comparison of Premier(TM) Rotaclone(®), ProSpecT(TM), and RIDASCREEN(®) Rotavirus Enzyme Immunoassay Kits for Detection of Rotavirus Antigen in Stool Specimens - Gautam, Rashi (J Clin Virol, 2013)
BACKGROUND: Rotaviruses are the major cause of severe dehydrating diarrhea in children throughout the world. Enzyme immunoassays (EIA) have been the standard method for detection of rotavirus in stool specimens since the 1980s. The World Health Organization (WHO) Rotavirus Surveillance Network has proposed including three EIA kits in the WHO-GSM (Global Management System/Système Mondial de Gestion ) catalogue for easy procurement of EIA kits by participating rotavirus surveillance network laboratories. OBJECTIVES: In this study, we conducted a comparative analysis of 3 commercially available enzyme immunoassay kits: Premier(TM) Rotaclone(®) (Meridian Bioscience, Inc.), ProSpecT(TM) (Oxoid, Ltd.) and RIDASCREEN(®) (R-biopharm AG) for rotavirus diagnostics. STUDY DESIGN: Using reverse-transcriptase-PCR (RT-PCR) as the gold standard, the 3 EIA kits were evaluated by testing a stool panel consisting of 56 rotavirus-positive and 54 rotavirus negative samples. RESULTS: The sensitivities of the Premier(TM) Rotaclone(®), ProSpecT(TM) and RIDASCREEN(®) kits were 76.8%, 75% and 82.1% respectively, but did not differ significantly. The specificity of all the 3 kits was 100%. The use of RT-PCR as a gold standard lowered the observed sensitivity of all 3 EIA kits but helps to reduce equivocal results that can be seen when another EIA or other non-molecular methods are used as the reference assay in comparison studies. CONCLUSION: Our study found that all three kits are suitable for use by rotavirus surveillance programs.